Analysis of consumption pattern of livestock products and its demand elasticities of Indian households: Evidence from NSSO data - Gowri , S R; Malaisamy, A; Raswanthkrishna, M (Plant Science Today, 2025)
The present study aims to examine the consumption pattern and price elasticities of livestock products among rural and urban households in India, utilizing household consumption expenditure survey data for the year 2021-22. It provides insights into budget allocations and consumer responses to price fluctuations. The Almost Ideal Demand System (AIDS) model has been employed to estimate the elasticities. Milk, chicken and eggs dominate livestock-related expenditure, accounting for nearly 80 % of total spending. Milk alone represents 38.45 % of the budget, highlighting its status as a dietary staple, while chicken and eggs follow with shares of 20.09 % and 19.34 %, respectively. Other products such as fish, mutton, beef and pork hold smaller proportions, with fish contributing 13.12 %. The own-price elasticities indicate that the demand for milk, eggs and chicken is inelastic, meaning consumption remains relatively stable despite changes in price . In contrast, beef, mutton and pork though accounting for a smaller portion of total livestock spending, display demand patterns that are either positive or nearly inelastic in response to price changes, suggesting their consumption is concentrated among specific population segments. Cross-price elasticity estimates reveal limited substitutability among major livestock products. These findings underscore the essential role of milk, eggs and chicken in Indian diets and offer valuable insights for policymakers and market strategists aiming to address food security and nutrition in diverse demographic settings.